Estimated plasma volume status: association with congestion, cardiorenal syndrome and prognosis in precapillary pulmonary hypertension - Yogeswaran, Athiththan; Richter, Manuel J.; Husain-Syed, Faeq; Rako, Zvonimir; Sommer, Natascha; Grimminger, Friedrich; Seeger, Werner; Ghofrani, Hossein Ardeschir; Gall, Henning; Tello, Khodr (Frontiers in Cardiovascular Medicine, 2023)
Background: Volume overload is often associated with clinical deterioration in precapillary pulmonary hypertension (PH). However, thorough assessment of volume overload is complex and therefore not routinely performed. We examined whether estimated plasma volume status (ePVS) is associated with central venous congestion and prognosis in patients with idiopathic pulmonary arterial hypertension (IPAH) or chronic thromboembolic PH (CTEPH). Methods: We included all patients with incident IPAH or CTEPH enrolled in the Giessen PH Registry between January 2010 and January 2021. Plasma volume status was estimated using the Strauss formula. Results: In total, 381 patients were analyzed. Patients with high ePVS (≥ 4.7 mL/g vs < 4.7 mL/g) at baseline showed significantly increased central venous pressure (CVP; median [Q1, Q3]: 8 [5, 11] mmHg vs 6 [3, 10] mmHg) and pulmonary arterial wedge pressure (10 [8, 15] mmHg vs 8 [6, 12] mmHg), while right ventricular function was not altered. In multivariate stepwise backward Cox regression, ePVS was independently associated with transplant-free survival at baseline and during follow-up (hazard ratio [95% confidence interval]: 1.24 [0.96, 1.60] and 2.33 [1.49, 3.63], respectively). An intra-individual decrease in ePVS was associated with a decrease in CVP and predicted prognosis in univariate Cox regression. Patients with high ePVS without edema had lower transplant-free survival than those with normal ePVS without edema. In addition, high ePVS was associated with cardiorenal syndrome. Conclusions: In precapillary PH, ePVS is associated with congestion and prognosis. High ePVS without edema may represent an under-recognized subgroup with poor prognosis.